Molecular diversity of soil ciliates in Borneo tropical secondary forests - Lee, Ting Ting; Wong, Sing King; Lau, Wei Hong; Ahmad Ali, Siti Ramlah (Research India Publications, 2014)
Ciliates are unicellular eukaryotes and play important roles in soil processes. Their significant contributions in soil cause the growing interest in studying soil ciliates for monitoring biodiversity and soil quality. However, knowledge of their regional and global diversity is insufficient due to the limits of the conventional methods. Thus, the objective of this study was to investigate the diversity of soil ciliates in Borneo (Bintulu, Sarawak) using semi-nested polymerase chain reaction reaction-denaturing gradient gel electrophoresis (PCR-DGGE). Soil samples were collected in two tropical secondary forests from December 2010 to June 2011. Primer sets EukA/CilDGGE-r and CilF- GC/CilDGGE-r were used in semi-nested PCR to amplify soil ciliate 18S rDNA. DGGE profiles revealed a total of 83 predominant bands which were then excised and sequenced. Majority (99%) of these bands matched ciliate 18S rDNA in the GenBank with the similarity of 91% and above. Phylogenetic analysis showed that these sequences belonged to 34 species which affiliated to 6 classes, 13 orders, 17 families and 19 genera. The forest soils were dominated by Litostomatea, Colpodea, Spirotrichea and Oligohymenophorea, followed by two rare groups which were the Armophorea and Heterotrichea. Statistical analyses revealed that the diversity and community structure of soil ciliates were different among the sampling sites and across time. The semi-nested PCR-DGGE approach in this study has served as a fast and useful method in studying soil ciliates. New combinations of primer sets presented herein contributed to the choices of 18S rDNA specific primers for PCR-DGGE analysis of soil ciliates. Our findings revealed an insight into the diversity of soil ciliates in Borneo tropical secondary forests.